Free-Energy and Illusions: The Cornsweet Effect - Brown, Harriet (Frontiers Research Foundation, 2012)
In this paper, we review the nature of illusions using the free-energy formulation of Bayesian perception. We reiterate the notion that illusory percepts are, in fact, Bayes-optimal and represent the most likely explanation for ambiguous sensory input. This point is illustrated using perhaps the simplest of visual illusions; namely, the Cornsweet effect. By using plausible prior beliefs about the spatial gradients of illuminance and reflectance in visual scenes, we show that the Cornsweet effect emerges as a natural consequence of Bayes-optimal perception. Furthermore, we were able to simulate the appearance of secondary illusory percepts (Mach bands) as a function of stimulus contrast. The contrast-dependent emergence of the Cornsweet effect and subsequent appearance of Mach bands were simulated using a simple but plausible generative model. Because our generative model was inverted using a neurobiologically plausible scheme, we could use the inversion as a simulation of neuronal processing and implicit inference. Finally, we were able to verify the qualitative and quantitative predictions of this Bayes-optimal simulation psychophysically, using stimuli presented briefly to normal subjects at different contrast levels, in the context of a fixed alternative forced choice paradigm.